2017
DOI: 10.1002/cplu.201600651
|View full text |Cite
|
Sign up to set email alerts
|

A Mycoplasma Genomic DNA Probe using Gated Nanoporous Anodic Alumina

Abstract: An anoporous anodica lumina( NAA)-based sensors ystem for the detection of Mycoplasma was developed through the implementation of "molecular gates" selectivet ot he presence of this bacterium. The capped support showed an egligible cargo release, while presence of Mycoplasma genomic DNA resulted in the release of rhodamine Bf luorescent dye. This sensor system presentsalimit of detection of 20 genomic DNA co-pies·mL À1 and was applied to the detection of Mycoplasma bacteria in competitive environments, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Ethanol is a common electrolyte additive that enables to perform anodization below 0 °C reaching lower current densities. It allows to yield even smaller pores, for example 8 nm diameter pores for the sulfuric-NAA [26,96,97]. It was recently demonstrated that addition of ethanol improves the formation of NAA in sulfuric acid, suppressing its chemical dissolution and the anodization rate.…”
Section: Electrolyte Specific Naa Geometrymentioning
confidence: 99%
“…Ethanol is a common electrolyte additive that enables to perform anodization below 0 °C reaching lower current densities. It allows to yield even smaller pores, for example 8 nm diameter pores for the sulfuric-NAA [26,96,97]. It was recently demonstrated that addition of ethanol improves the formation of NAA in sulfuric acid, suppressing its chemical dissolution and the anodization rate.…”
Section: Electrolyte Specific Naa Geometrymentioning
confidence: 99%
“…The results were compared with PCR method, obtaining comparable results in terms of selectivity and sensitivity. Closely related materials but using nanoporous anodic alumina instead of mesoporous silica were recently developed for the detection Candida albicans [39] and Mycoplasma fermentans [40].…”
Section: Systems Based On Gated Materialsmentioning
confidence: 99%
“…SAMs of silanes with hydrophobic terminal groups increase the hydrophobicity of NAA [ 107 ], SAMs of perfluoroalkylchorosilanes reduce the effective pore diameter of NAA for molecular transport [ 108 ], poly(ethylene glycol)silane SAMs improve the biocompatibility of NAA for immunoisolation [ 109 ], and SAMs of mercaptosilanes have been used for sensing applications [ 110 , 111 , 112 , 113 ]. Similar to SAMs of alkanoic and phosphonic acids, SAMs of organosilanes can act as chemical linkers for further immobilization of biomolecules [ 114 , 115 , 116 ], polymers [ 116 ], and nanoparticles [ 117 ]. Furthermore, organosilanes containing different terminal functionalities (e.g., amine, thiol, carboxyl, etc.)…”
Section: Surface Modification Of Nanoporous Anodic Alumina Photonimentioning
confidence: 99%